Prediction and Characterization of Cationic Arginine-Rich Plant Antimicrobial Peptide SM-985 From Teosinte (Zea mays ssp. mexicana) - Qutb, Abdelrahman M.; Wei, Feng; Dong, Wubei (Frontiers in Microbiology, 2020)
Antimicrobial peptides (AMPs) are effective against different plant pathogens and newly considered as part of plant defense systems. From prokaryotes to eukaryotes, AMPs can exist in all forms of life. SM-985 is a cationic AMP isolated from the cDNA library of Mexican teosinte (Zea mays ssp. mexicana). A computational prediction server running with different algorithms was used to screen the teosinte cDNA library for AMPs, and the SM-985 peptide was predicted as an AMP with high probability prediction values. SM-985 is an arginine-rich peptide and composed of 21 amino acids (MW: 2671.06 Da). The physicochemical properties of SM-985 are very promising as an AMP, including the net charge (+8), hydrophobicity ratio of 23%, Boman index of 5.19 kcal/mol, and isoelectric point of 12.95. The SM-985 peptide has amphipathic α-helix conformations. The antimicrobial activity of SM-985 was confirmed against 6 bacterial plant pathogens, and the MIC of SM-985 against Gram-positive indicators was 8 μM, while the MIC of SM-985 against Gram-negative indicators was 4 μM. The SM-985 interacting with the bacterial membrane and this interaction were examined by treatment of the bacterial indicators with FITC-SM-985 peptide, which showed a high binding affinity of SM-985 to the bacterial membrane (whether Gram-positive or Gram-negative). Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images of the treated bacteria with SM-985 demonstrated cell membrane damage and cell lysis. In vivo antimicrobial activity was examined, and SM-985 prevented leaf spot disease infection caused by Pst DC3000 on Solanum lycopersicum. Moreover, SM-985 showed sensitivity to calcium chloride salt, which is a common feature of cationic AMPs.